Microneedle patch based on curcumin-loaded ZIF-67 nanoparticles as well as preparation method and application of microneedle patch

Through the sequential release mechanism of Cur@ZIF-67NPs, the multifunctional microneedle patch HP@CZ MN was prepared, which solved the problem of imbalance in antibiotic resistance and immune response in the treatment of periodontitis, and achieved the synergistic treatment effect of antibacterial, anti-inflammatory and osteogenesis.

CN120242066APending Publication Date: 2025-07-04TIANJIN DENTAL HOSPITAL
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510506530.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-22
Publication Date
2025-07-04

AI Technical Summary

Technical Problem

There is an antibiotic resistance problem in the existing treatment of periodontitis, and traditional treatment methods are difficult to effectively regulate immune response and bone remodeling, resulting in poor treatment results.

Method used

Complex nanoparticles Cur@ZIF-67NPs were used to quickly release Co2+ to regulate macrophage polarization through ZIF-67 nanomaterials, and slow release of curcumin regulates periodontal membrane stem cell differentiation. Multifunctional microneedle patch HP@CZ MN was prepared to achieve sequential release of active substances, combining antibacterial, anti-inflammatory and promoting osteopathic effects.

Benefits of technology

It significantly improves the effect of periodontitis treatment. Through rapid anti-inflammatory and slow osteogenesis regulation, the triple synergy of antibacterial, anti-inflammatory and bone-promoting effect is achieved, overcoming the problems of insufficient stability and bioavailability of curcumin, and providing a safe and efficient drug delivery system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120242066A_ABST
    Figure CN120242066A_ABST
Patent Text Reader

Abstract

The invention provides a composite nanoparticle with active substance sequential release capability, a multifunctional microneedle patch based on curcumin-loaded ZIF-67 nanoparticles, preparation methods of the composite nanoparticle and the multifunctional microneedle patch and application of the multifunctional microneedle patch, and belongs to the technical field of biology. The composite nano-particles with the active substance sequential release capability are CurZIF-67NPs, the average particle size is 403 + / -7 nm, the microstructure is dodecahedral structure particles with rough textures on the surface, and the composite nano-particles have the effects of slowly releasing bioactive substances, improving the inflammatory microenvironment and regulating and controlling osteogenesis under certain conditions. The composite nano-particle comprises curcumin powder and a ZIF-67 nano-material, the ZIF-67 nano-material can be decomposed to quickly release Co < 2 + >, macrophages are regulated and controlled to be polarized to an M2 type, and excessive immune inflammation reaction is improved; the curcumin powder is slowly released, so that the periodontal ligament stem cells can be regulated and controlled to be differentiated into osteoblasts, and the osteogenic activity is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of biotechnology, and particularly relates to a microneedle patch based on curcumin-loaded ZIF-67 nanoparticles, a preparation method and an application thereof, mainly focusing on the construction of an innovative auxiliary drug delivery system and applying it to the clinical adjuvant treatment of periodontitis. Background Art

[0002] Periodontitis is a chronic inflammatory disease resulting from the continuous destruction of the periodontal supporting tissues (gingiva, periodontal ligament, alveolar bone and cementum) by dental plaque bacteria. If not intervened in time, it will lead to gradual loosening and loss of teeth. The pathogenesis of periodontitis is complex, involving complex interactions of bacterial infection, inflammatory response and immune response. In the initial stage, dental plaque bacteria release toxins and metabolites, directly attacking the periodontal tissues and triggering the body's defensive inflammatory response. However, under the pathological background of periodontitis, these responses often become excessive, leading to a large influx of immune cells and inflammatory mediators, causing significant tissue damage, manifested as gingival swelling, bleeding and pain. In addition, continuous inflammation activates osteoclasts, accelerates bone resorption, forms bone defects, further weakens the supporting effect of teeth, increases the risk of tooth loss, and forms a vicious cycle.

[0003] Early treatment strategies include mechanical debridement combined with the application of antibiotics. Although it can improve the curative effect, the long-term use of antibiotics is likely to lead to drug resistance problems. Therefore, the development of new non-antibiotic antibacterial regimens has become an urgent need, aiming to effectively inhibit bacteria while avoiding the generation of drug resistance. At the same time, it has been found that the core pathogenesis of periodontitis lies in the imbalance of the ratio of anti-inflammatory and pro-inflammatory phagocytes and the disorder of the immune response system, prompting the treatment idea to shift to regulating the function of immune cells.

[0004] In addition, the problem of bone remodeling cannot be ignored in the treatment of periodontitis. For patients with severe periodontitis, guided tissue regeneration surgery (GTR) is a commonly used surgical method. However, in complex cases such as patients with narrow and deep periodontal pockets, during the clinical treatment process, it faces problems such as a long treatment cycle, large trauma and difficult cleaning, and it is difficult to be completely cured. Therefore, researchers have introduced an auxiliary drug delivery system, utilizing the potential of autologous tissue regeneration, guiding cell migration and regulating the microenvironment to induce tissue regeneration by loading bioactive substances. Combining local drug treatment, especially developing a multifunctional material delivery system to achieve the synergistic effects of antibacterial, anti-inflammatory and bone regeneration promotion, has become a research hotspot and challenge in the treatment of periodontitis. Summary of the Invention

[0005] The purpose of this application is to provide a multifunctional microneedle patch with composite nanoparticles and the ability of sequential release of active substances, a preparation method and an application thereof, so as to solve the technical problems mentioned in the background art.

[0006] To solve the above technical problems, the specific technical solutions of this application are as follows.

[0007] The first aspect of the present application relates to a composite nanoparticle having the ability to sequentially release active substances. The composite nanoparticle is Cur@ZIF-67NPs, with an average particle size of 403nm±7nm, and a microstructure of dodecahedral structure particles with a rough texture on the surface. It has the function of slowly releasing bioactive substances under certain conditions, improving the inflammatory microenvironment, and regulating osteogenesis.

[0008] The second aspect of the present application relates to a multifunctional microneedle (MN) having the capability of sequentially releasing active substances, wherein the MN comprises the above-mentioned Cur@ZIF-67NPs.

[0009] The third aspect of the present application relates to a multifunctional microneedle patch capable of sequentially releasing active substances. The multifunctional microneedle patch is HP@CZ MN, which includes a transparent substrate and yellow-brown MNs covering the surface of the substrate, and the interior of the MN is filled with the above-mentioned Cur@ZIF-67NPs.

[0010] Furthermore, the diameter of the substrate is 270 μm, the tip length of the MN is 650 μm, and the distance between the tips is 550 μm.

[0011] The fourth aspect of the present application relates to a method for preparing a multifunctional microneedle patch as described above, comprising: S1, using a solvent impregnation method to fully disperse curcumin powder in a solvent, adding ZIF-67 nanomaterials to coat the curcumin powder with the ZIF-67 nanomaterials, washing and drying to obtain reddish-brown solid Cur@ZIF-67NPs; S2, fully mixing methacryloyl hyaluronic acid (HAMA) and methacryloyl polylysine (PLMA) to obtain a mixed solution, and fully dispersing Cur@ZIF-67NPs in the mixed solution to obtain a microneedle precursor solution; S3, injecting the microneedle precursor solution into a PDMS mold, degassing under negative pressure, drying and concentrating, and irradiating with a 405nm light source to form an MN; then dripping a 20% (w / v) polyvinyl alcohol (PVA) solution, drying to form a substrate, and demolding to obtain a multifunctional microneedle patch HP@CZ MN loaded with Cur@ZIF-67NPs.

[0012] In an acidic microenvironment, the ZIF-67 nanomaterial framework can rapidly decompose and release Co 2+ , regulating the polarization of macrophages to M2 type, effectively improving excessive immune inflammatory response; then, the curcumin powder encapsulated in the porous structure of ZIF-67 nanomaterials is slowly released, thereby regulating the differentiation of periodontal ligament stem cells (PDLSCs) into osteoblasts, significantly enhancing osteogenic activity.

[0013] Further, step S1 satisfies at least one of the following: (1) The mass ratio of curcumin powder to ZIF-67 nanomaterial is 1:200 - 1:300; (2) The mixing time of curcumin powder and ZIF-67 nanomaterial is 18 hours - 24 hours, and the reaction temperature is room temperature under normal pressure; (3) The drying conditions of Cur@ZIF-67 NPs are 120 °C and the drying time is 24 hours - 36 hours.

[0014] Further, step S2 satisfies at least one of the following: (1) The final concentration range of HAMA and PLMA in the mixed solution is 2% - 10%, and the final concentration values are the same; (2) In the micro-needle precursor solution, the mass fraction of Cur@ZIF-67 NPs is 0.05 wt% - 1 wt%.

[0015] Further, during the process of preparing MN in step S3, at least one of the following is satisfied: (1) The negative pressure defoaming operation and the drying and concentration operation are each performed twice. The single negative pressure defoaming time is 13 minutes - 25 minutes, the drying and concentration temperature is 30 °C - 37 °C, and the single drying and concentration time is 5 hours - 8 hours; (2) The micro-needle precursor solution completely covers the tip part of the PDMS mold; (3) Irradiate with a 405 nm light source for 10 seconds - 20 seconds, and operate at room temperature under normal pressure.

[0016] Further, during the process of preparing the substrate in step S3, the drying time is 24 hours - 48 hours.

[0017] The fifth aspect of the present application relates to an application of HP@CZ MN, which is prepared by the above preparation method. The application of HP@CZ MN in the adjuvant treatment of periodontitis includes at least one of the following: (1) Antibacterial; (2) Regulating the inflammatory microenvironment; (3) Promoting osteogenic differentiation.

[0018] The present application has the following beneficial effects:

[0019] (1) The present application relates to a composite nanoparticle Cur@ZIF-67 NPs with the ability of sequential release of active substances. The Cur@ZIF-67 NPs use ZIF-67 nanomaterial as the structural framework to achieve efficient encapsulation of curcumin powder. This technological breakthrough greatly overcomes the challenges of low bioavailability and insufficient stability faced by curcumin in direct application. By optimizing the encapsulation and release mechanism of curcumin, Cur@ZIF-67 NPs not only significantly improve the stability and persistence of Cur, but also greatly expand its application potential, laying a solid foundation for subsequent studies on drug release kinetics, biological activity evaluation and clinical application, and showing great prospects in the fields of inflammation regulation and bone tissue regeneration.

[0020] (2) The present application relates to a multifunctional microneedle patch HP@CZ MN with the ability to sequentially release active substances. The microneedles of the multifunctional microneedle patch contain PLMA components, which can play an excellent role in removing periodontal pathogens. In addition, due to the Cur@ZIF-67NPs contained in it, the multifunctional microneedle patch can simultaneously achieve antibacterial effects, regulate inflammatory responses, and promote osteogenic differentiation of cells. Based on these effects, the ultimate goal of treating periodontitis is achieved. The HP@CZ MN has achieved remarkable results in material ratio, structural design, performance characterization, and application evaluation. It can accurately match the complex pathogenesis of periodontitis and be used for the adjuvant treatment of periodontitis. It not only opens up a new treatment path for the repair and regeneration of periodontal tissues, but also lays a solid and scientific foundation for its clinical application, indicating that it will bring significant and lasting beneficial effects in promoting periodontal health and restoring oral function.

[0021] (3) The present application relates to a method for preparing HP@CZ MN with the ability to sequentially release active substances. The method for preparing HP@CZ MN is simple to operate and can accurately shape a uniform microneedle structure, meeting the basic requirements for transdermal drug delivery. HP@CZ MN exhibits excellent process performance during the preparation process: its suitable swelling properties ensure the effective release and penetration of the drug; stable mechanical strength ensures the structural integrity and durability of the patch during use; coupled with good rheological properties, it further improves the adaptability and safety of the patch in complex application environments. This series of advantages highlights the advanced nature and practicality of the HP@CZ MN preparation method, indicating that it will play an immeasurable role in improving treatment efficiency and ensuring patient safety.

[0022] (4) The present application relates to the application of an HP@CZ MN with the ability to sequentially release active substances, which integrates the triple effects of antibacterial, anti-inflammatory and osteogenesis. The HP@CZ MN has shown extraordinary application potential in the field of periodontitis treatment due to its unique ability to sustain the release of active substances. Through a carefully designed drug release mechanism, HP@CZ MN can not only effectively inhibit the growth of pathogens in the early stage of treatment, but also reduce the inflammatory response through the sudden release of cobalt ions in the middle stage. In the later stage of treatment, it also performs well in promoting the osteogenesis regeneration of periodontal tissues through sustained-release curcumin, achieving the triple synergistic effects of antibacterial, anti-inflammatory and osteogenesis. This innovative achievement not only lays a solid foundation for the widespread application of HP@CZ MN in periodontal treatment and other biomedical fields, but also opens up broad prospects for promoting progress in the biomedical field, improving patients' oral health and overall quality of life, and showing far-reaching positive impacts. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] To more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the following will briefly introduce the accompanying drawings required for the description of the embodiments or the prior art.

[0024] Figure 1 Schematic diagram for the preparation of Cur@ZIF-67 NPs shown in Example 1;

[0025] Figure 2 Transmission electron microscope images and particle size distribution diagrams of ZIF-67 and Cur@ZIF-67 NPs;

[0026] Figure 3 X-ray diffraction patterns of Cur, ZIF-67, and Cur@ZIF-67 NPs;

[0027] Figure 4 Fourier transform infrared spectra of Cur, ZIF-67, and Cur@ZIF-67 NPs;

[0028] Figure 5 Study on the improvement of the photodegradation rate of Cur by Cur@ZIF-67;

[0029] Figure 6 Flow chart for the preparation of HP@CZ MN;

[0030] Figure 7 Volume view and scanning electron microscope images of HP@CZ MN;

[0031] Figure 8 Sequential release study of cobalt ions and curcumin in HP@CZ MN;

[0032] Figure 9 In vitro and in vivo biosafety detection of HP@CZ MN;

[0033] Figure 10 In vitro antibacterial performance of HP@CZ MN;

[0034] Figure 11 Study on the in vitro regulation of the inflammatory microenvironment by HP@CZ MN;

[0035] Figure 12 Study on the in vitro promotion effect of HP@CZ MN on periodontal bone regeneration;

[0036] Figure 13 Evaluation of the in vivo therapeutic effect of HP@CZ MN on a rat periodontitis model. Detailed implementation manners

[0037] The technical solution of the present application will be explained in more detail below. The present application is not limited by the following description. Unless otherwise specified, all technical and scientific terms used in the present application have the same meaning as commonly understood by those of ordinary skill in the art to which the present application pertains. Without departing from the scope or spirit of the present application, various improvements and changes can be made to the specific embodiments of the present application specification. The present application specification and embodiments are merely exemplary.

[0038] In view of the limitations in the current technical field, after long-term in-depth research and extensive practical exploration by the applicant, the technical solution of this invention has finally been creatively proposed. To better understand the purpose, structure, and function of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings. Except for special regulations otherwise, the reagents used in the embodiments of the present invention can all be obtained by purchasing commercially. The core of the solution involved in the present application lies in the design of an MN patch loaded with an active ingredient, and it is innovatively applied to the treatment of a rat periodontitis model, aiming to serve as an effective auxiliary means for the existing clinical treatment plan for periodontitis, with the expectation of significantly improving the long-term treatment effect of periodontitis.

[0039] Metal-organic frameworks (MOFs), as a class of porous crystalline materials formed by the self-assembly of metal ions or metal clusters with organic ligands, have shown great application potential in the fields of gas separation, catalysis, energy storage, and biomedicine due to their highly ordered pore structures, adjustable pore sizes, rich chemical compositions, and good biocompatibility. Among them, zeolitic imidazolate framework materials (ZIFs), as an important branch of MOFs, have received extensive attention due to their excellent stability and easy synthesis characteristics. In particular, ZIF-67, formed by the coordination of Co 2+ with 2-methylimidazole, is an ideal candidate material in the field of drug loading and delivery. The porous structure of ZIF-67 enables drug molecules to easily enter its interior to achieve efficient loading, while its good biocompatibility ensures that the material will not cause adverse reactions in the body, providing a strong guarantee for the safe delivery of drugs. Combining the characteristics of nanoparticles (NPs) such as small size and large surface area to better play their roles.

[0040] Curcumin (Cur) is a natural polyphenol compound derived from the rhizome of turmeric, which has attracted much attention due to its wide range of biological activities. Curcumin has multiple pharmacological effects such as anti-inflammatory, antioxidant, anti-tumor and neuroprotective, and is regarded as a highly promising drug candidate molecule; however, its poor water solubility, low stability and low bioavailability limit its clinical application. Therefore, developing a carrier that can effectively load curcumin and improve its stability and bioavailability is of great significance for expanding the application range of curcumin and realizing its clinical value. ZIF-67 is an ideal choice to solve this problem. They can serve as efficient carriers of curcumin, achieve stable loading and controllable release of drugs, and open up a new path for the clinical application of curcumin.

[0041] Microneedle (MN) patch technology uses tiny needles to penetrate the skin surface or mucous membrane in a nearly painless and minimally invasive manner, directly delivering drugs to subcutaneous tissue or specific lesion areas, thereby effectively solving the problems of poor drug permeability, low bioavailability, and frequent drug administration in traditional drug delivery methods. In addition, the versatility of microneedle patches is also a highlight. It can flexibly load a variety of drugs and therapeutic molecules including antibiotics and growth factors, fully meeting the diverse needs of clinical treatment. Through carefully designed materials and structures, microneedle patches can also achieve controlled release of drugs, further meeting the requirements of personalized treatment.

[0042] The multifunctional microneedle patch HP@CZ MN with the ability to sequentially release active substances of the present invention comprises a transparent substrate, yellow-brown multifunctional microneedle MN covering the surface of the substrate, and the MN is filled with composite nanoparticles Cur@ZIF-67NPs. HP@CZ MN has certain applications in the adjuvant treatment of periodontitis, can resist bacteria, regulate the inflammatory microenvironment, and promote osteogenic differentiation. The preparation method is specifically as follows:

[0043] S1. Using an improved solvent impregnation method, the curcumin powder is fully dispersed in a solvent, and ZIF-67 nanomaterials are added. The mass ratio of the curcumin powder to the ZIF-67 nanomaterials is 1:200-1:300. The curcumin powder and the ZIF-67 nanomaterials are uniformly mixed at room temperature under normal pressure for 18 hours to 24 hours, so that the ZIF-67 nanomaterials fully cover the curcumin powder. The mixture is washed and dried at 120° C. for 24 hours to 36 hours to obtain reddish-brown solid Cur@ZIF-67NPs. The obtained Cur@ZIF-67NPs have an average particle size of 403nm±7nm, and the microstructure is a dodecahedral structure particle with a rough texture on the surface, which has the functions of slowly releasing bioactive substances, improving the immune microenvironment and regulating osteogenesis under certain conditions;

[0044] S2. Thoroughly mix methacrylated hyaluronic acid (HAMA) and methacrylated polylysine (PLMA) to obtain a mixed solution (HAMA-PLMA mixed solution), ensuring that the final concentrations of HAMA and PLMA in the mixed solution are 2% - 10% and their final concentration values are the same. Disperse Cur@ZIF-67 NPs thoroughly in the HAMA-PLMA mixed solution to obtain a micro-needle precursor solution, and the mass fraction of Cur@ZIF-67 NPs in the micro-needle precursor solution is 0.05 wt% - 1 wt%.

[0045] S3. Inject the micro-needle precursor solution into the PDMS mold until the tip part of the PDMS mold is completely submerged. After two rounds of negative pressure degassing (single time is 13 minutes - 25 minutes), two rounds of drying and concentration (single time is 5 hours - 8 hours, drying and concentration temperature is 30°C - 37°C), and irradiating with a 405 nm light source at room temperature under normal pressure for 10 seconds - 20 seconds to form MN. Then dropwise add a 20% (w / v) polyvinyl alcohol (PVA) solution, dry for 24 hours - 48 hours to form a substrate, and demold to obtain a multifunctional micro-needle patch HP@CZ MN loaded with Cur@ZIF-67 NPs. The tip length of the MN of HP@CZ MN is 650 μm, the distance between the tips is 550 μm, and the diameter of the substrate is 270 μm.

[0046] Example 1

[0047] This example provides a Cur@ZIF-67 NPs with the ability of sequential release of active substances, the corresponding multifunctional micro-needle patch HP@CZ MN, and its preparation method.

[0048] A composite nanoparticle Cur@ZIF-67 NPs with the ability of sequential release of active substances, with an average particle size of 403 nm ± 7 nm, and a microstructure of dodecahedral particles with rough textures on the surface. It has the functions of slowly releasing bioactive substances under certain conditions, improving the inflammatory microenvironment, and osteogenic regulation, and is a solid substance showing reddish-brown in the naked eye.

[0049] A multifunctional micro-needle patch HP@CZ MN with the ability of sequential release of active substances, including a transparent substrate and yellowish-brown MN covering the surface of the substrate. The diameter of the substrate is 270 μm, the tip length of the MN is 650 μm, the tip distance is 550 μm, and the interior of the tip of the MN is filled with the above-mentioned Cur@ZIF-67 NPs. The preparation method specifically includes:

[0050] S1. Prepare Cur@ZIF-67 NPs

[0051] In this example, the solvent impregnation method is used to prepare Cur@ZIF-67 NPs. As Figure 1As shown, first, 0.37 mg of Cur powder was dissolved in 10 mL of absolute ethanol and stirred at 600 rpm for 10 minutes at room temperature to ensure uniform dispersion; second, 100 mg of ZIF-67 nanomaterials were added and stirring continued at 600 rpm for 24 hours to fully coat Cur with ZIF-67; after stirring, the reddish-brown precipitate was filtered and washed repeatedly with absolute ethanol to remove impurities and residual solvents; finally, the reddish-brown precipitate was dried at 120 °C for 24 hours to ensure the stability of its structure, and the composite nanoparticles Cur@ZIF-67 NPs were successfully prepared.

[0052] S2. Preparation of the microneedle precursor solution

[0053] 10% methacrylated hyaluronic acid (HAMA) solution and 10% methacrylated polylysine (PLMA) solution were respectively prepared using a photoinitiator, and they were mixed in a 1:1 ratio to obtain a mixture with a final concentration of 5% for both HAMA and PLMA; 1 mg of Cur@ZIF-67 NPs powder was weighed and dissolved in a small amount of dimethyl sulfoxide, and then added to 1 mL of the aforementioned HAMA-PLMA mixture, and sonicated to mix evenly to ensure the uniform dispersion of the NPs, and the microneedle precursor solution was prepared.

[0054] S3. Preparation of the multifunctional microneedle patch HP@CZ MN

[0055] HP@CZ MN was prepared by the perfusion method. As Figure 6 shown, a PDMS mold was prepared, the microneedle precursor solution was injected into the PDMS mold to ensure complete coverage of the mold, degassed under negative pressure twice for 15 minutes each time, and then subjected to two heating and drying concentration treatments, each at 30 °C for at least 6 hours. After the heating and concentration were completed, the microneedle precursor solution was irradiated with a 405 nm light source for 10 to 20 seconds to ensure complete curing of the microneedle precursor solution to form the microneedle tip; subsequently, a 20% (w / v) polyvinyl alcohol (PVA) solution was dropped onto the tip of the already cured MN, heated and dried to form a stable substrate, demolded, and finally the multifunctional microneedle patch HP@CZ MN loaded with Cur@ZIF-67 NPs was obtained.

[0056] Comparative Example 1

[0057] This comparative example provides a common patch HP MN. The preparation method of this patch HP MN is basically the same as that of Example 1, except that: it does not include Cur@ZIF-67 NPs, and only the perfusion method is used to prepare the patch to obtain MN and the substrate, and drying treatment is carried out to enhance the strength and stability of the patch, and the common patch HP MN is obtained.

[0058] Comparative Example 2

[0059] This comparative example provides a patch HP@Z MN. The preparation method of this patch is basically the same as that of Comparative Example 1, except that: it does not include Cur@ZIF-67 NPs and only contains ZIF-67 nanomaterials. Specifically, 1 mg of ZIF-67 powder is weighed and dissolved in a small amount of DMSO, and then added to 1 mL of the HAMA-PLMA mixture to obtain the micro-needle precursor solution of HP@Z MN. Finally, HP@Z MN is prepared by the perfusion method.

[0060] Comparative Example 3

[0061] This example provides a patch HP@C MN. The preparation method of this patch is basically the same as that of Comparative Example 1, except that: it does not include Cur@ZIF-67 NPs and only contains Cur powder. Specifically, a 10 mM curcumin mother liquor is prepared with DMSO, and 1 μL of the mother liquor is taken and added to 1 mL of the HAMA-PLMA mixture to obtain the micro-needle precursor solution of HP@C MN. Finally, HP@C MN is prepared by the perfusion method.

[0062] Test Example 1

[0063] To verify whether Cur@ZIF-67 NPs are successfully prepared, the following determinations are carried out.

[0064] 1. Transmission electron microscopy (TEM) and particle size distribution determination of Cur@ZIF-67 NPs

[0065] Select ZIF-67 nanoparticles (ZIF-67 NPs) and Cur@ZIF-67 NPs prepared in Example 1 as test samples for TEM experiments to verify the crystal structure and microscopic morphology of ZIF-67 NPs; take pictures of ZIF-67 NPs and Cur@ZIF-67 NPs samples at an appropriate magnification to obtain the TEM images of ZIF-67 NPs and Cur@ZIF-67 NPs.

[0066] The particle size distribution experiment is carried out by dynamic light scattering (DLS) technology to detect the particle size and distribution of ZIF-67 NPs; an appropriate amount of ZIF-67 NPs and Cur@ZIF-67 NPs samples are dispersed in a solvent and measured by a DLS instrument to obtain particle size distribution data.

[0067] The results are as Figure 2 shown, Figure 2 A, 2B are the TEM image and particle size distribution histogram of ZIF-67 NPs in sequence, Figure 2 C, 2D are the TEM image and particle size distribution histogram of Cur@ZIF-67 NPs in sequence. Figure 2A. As can be seen from 2C, ZIF-67 NPs exhibit a regular dodecahedral crystal structure with a smooth surface, demonstrating a high degree of order. When Cur is loaded onto ZIF-67 NPs, the basic dodecahedral framework remains, but the crystal surface shows a rougher microtexture. Figure 2 B. As observed from 2D, the average particle size of ZIF-67 NPs is 363.97 ± 6.95 nm, and its polydispersity index (PDI) is 0.287 ± 0.054. The average particle size of Cur@ZIF-67 NPs increases to 403 ± 7 nm, and the PDI also increases to 0.938 ± 0.050.

[0068] 2. X-ray diffractometer (XRD) analysis of Cur@ZIF-67 NPs

[0069] Cur, ZIF-67 NPs, and the Cur@ZIF-67 NPs prepared in Example 1 were selected as test samples for XRD experiments. The test samples were scanned using an X-ray diffractometer at a scanning angle of 5° - 80° with a speed of 6° / min and a Co target.

[0070] Figure 3 The XRD patterns of Cur, ZIF-67 NPs, and Cur@ZIF-67 NPs are shown. As Figure 3 shown, significant diffraction peaks appear in the spectrum of Cur at specific diffraction angles. In contrast, the diffraction peaks of ZIF-67 NPs show different characteristics, reflecting its unique crystal structure. The XRD spectrum of Cur@ZIF-67 NPs contains the characteristic peaks of both Cur and ZIF-67 NPs, indicating the successful preparation of Cur@ZIF-67 NPs. However, the intensity and position of the peaks may be adjusted due to the interaction between the two materials, demonstrating the successful preparation of Cur@ZIF-67 NPs.

[0071] 3. Fourier transform infrared spectroscopy (FTIR) analysis of Cur@ZIF-67 NPs

[0072] Cur, ZIF-67 NPs, and the Cur@ZIF-67 NPs prepared in Example 1 were selected as test samples for FTIR experiments. The FTIR spectrometer was used to record and analyze the infrared absorption spectra of the test samples to reveal the chemical bond structures and interactions of Cur, ZIF-67 NPs, and their composites.

[0073] Figure 4FTIR spectra of Cur, ZIF-67 NPs, and Cur@ZIF-67 NPs. The infrared spectrum of Cur shows specific absorption peaks; the infrared spectrum of ZIF-67 NPs also presents a unique absorption peak pattern; the infrared spectrum of Cur@ZIF-67 NPs combines the characteristic peaks of Cur and ZIF-67 NPs, indicating the coexistence of the two in the composite material. Compared with individual Cur or ZIF-67 NPs, some absorption peaks of Cur@ZIF-67 NPs show shifts or intensity changes, which may be caused by the interaction (such as physical adsorption) between Cur and ZIF-67 NPs. The infrared spectral characteristics of Cur@ZIF-67 NPs not only confirm the successful loading of Cur onto ZIF-67 NPs but also reveal the possible changes in infrared spectral characteristics due to the interaction between the two, demonstrating the successful preparation of Cur@ZIF-67 NPs.

[0074] Experimental Example 2 Study on the Effect of Cur@ZIF-67 NPs on Improving the Photodegradation Rate of Cur

[0075] Select Cur powder and Cur@ZIF-67 NPs prepared in Example 1 as test samples, and conduct an experiment to determine the Cur concentration according to the ultraviolet absorption spectroscopy experimental standard to verify whether the stability of Cur is improved.

[0076] The specific test steps are as follows: Prepare a Cur solution and a Cur@ZIF-67 solution with a standard concentration of 1 mg / mL, expose these two solutions to sunlight, and observe their color changes; at the same time, regularly take 100 μL samples from each solution, appropriately dilute them with absolute ethanol, measure their OD values at a wavelength of 435 nm, and calculate the amount of Cur at each time point according to the standard curve to compare the stability differences between Cur and Cur@ZIF-67 solutions under the same conditions.

[0077] Figure 5 A shows the comparison of the color changes of Cur and Cur@ZIF-67 solutions after sunlight irradiation. Figure 5 B shows the stability analysis of Cur and Cur@ZIF-67 under continuous sunlight irradiation. Figure 5 It can be intuitively seen from A that as time prolongs, the color of the Cur solution changes significantly after sunlight irradiation, while the color of the Cur@ZIF-67 solution remains relatively stable. Figure 5Figure B shows the changes in the amount of Cur in the Cur and Cur@ZIF-67 solutions after 0 d, 1 d, 3 d, 5 d, and 7 d of continuous sunlight irradiation. It can be clearly seen from the figure that in the pure Cur solution, due to photolysis, its concentration decreased sharply since the 3rd day; while after encapsulation with ZIF-67 NPs, Cur was gradually released over time, effectively compensating for the amount of Cur degraded by light irradiation. It is fully proved that Cur@ZIF-67 NPs achieved a slow release effect of Cur and effectively improved the degradation rate of Cur under light irradiation.

[0078] Test Example 3

[0079] To verify whether HP@CZ MN was successfully prepared and its related properties, the following determinations were carried out.

[0080] 1. Morphology and Microtopography of HP@CZ MN

[0081] The HP@CZ MN prepared in Example 1 and the HP MN of Comparative Example 1 were selected as test samples, and the stereomicroscope and scanning electron microscope (SEM) were used to observe the morphology and microtopography of the microneedle patch.

[0082] Figure 7 Figures A and 7B are the stereoscopic view and SEM image of HP MN, Figure 7 Figures C and 7D are the stereoscopic view and SEM image of HP@CZ MN. Figure 7 Figures A and 7C show the macroscopic morphologies of HP MN and HP@CZ MN. It was clearly observed that the base diameter of the patch was 270 μm, ensuring a tight and stable fit between the patch and the gingiva, and at the same time providing a solid support basis for the microneedle structure. Figure 7 Figures B and 7D revealed the microstructural characteristics of HP MN and HP@CZ MN through SEM. The SEM images clearly showed that the surface of the patch was covered with microneedle structures, the tip height of which reached 650 μm, and the tip distance between the microneedles was 550 μm. This not only effectively avoided the mutual interference of MNs during penetration of the gingiva, reducing the potential damage to tissues, but also optimized the distribution and release effect of drugs, enabling the drugs to be more evenly distributed in the entire patch action area, thereby improving the treatment effectiveness and patient comfort.

[0083] 2. Sequential Release of Cobalt Ions (Co 2+ ) and Curcumin (Cur) from HP@CZ MN

[0084] Select the HP@CZ MN prepared in Example 1 and the HP@C MN of Comparative Example 3 as test samples, and use a UV-Vis spectrophotometer and inductively coupled plasma mass spectrometry (ICP-MS) to detect the release of Cur and Co respectively 2+ The release of 2+ was investigated. HP@C MN and HP@CZ MN were respectively immersed in PBS at pH 5.5 (simulating the inflammatory microenvironment). Samples were taken at regular intervals, and the release of Cur in the two groups of MN patches at each time point was detected with a UV-Vis spectrophotometer at a wavelength of 435 nm and quantified according to the standard curve. HP@CZ MN was immersed in PBS at pH 5.5, and samples were taken at the same time intervals. ICP-MS was used to measure the signal intensity of the isotope 59 Co in the HP@CZ MN patch group at each time point.

[0085] Figure 8 A represents the cumulative release amount of curcumin, Figure 8 B represents the cumulative release amount of cobalt ions. Figure 8 A shows that Cur in the HP@C MN patch was rapidly released within 7 days, and the release amount reached about 90%, showing a relatively rapid and concentrated release behavior. In contrast, Cur in the HP@CZ MN patch showed slow and controllable release characteristics within 30 days. This result proves that Cur encapsulated by ZIF-67 can achieve slow and sustained release in the acidic microenvironment of periodontitis, better meeting the long-term requirements of active substances during the periodontal tissue regeneration process. Figure 8 B shows that the release of Co 2+ showed an obvious burst release characteristic. This burst release pattern at the early stage is closely related to the degradation behavior of the MN patch, indicating that the rapid release of Co 2+ at the initial stage of periodontitis treatment can effectively inhibit the inflammatory response and play its unique anti-inflammatory role. This result proves that HP@CZ MN shows excellent sequential release performance of active substances in a simulated inflammatory microenvironment. The slow and controllable release of Cur and the 2+ burst release characteristic of Co at the early stage.

[0086] 3. Biocompatibility and safety evaluation of HP@CZ MN

[0087] Four kinds of microneedle patches prepared in Example 1 and Comparative Examples 1-3 were selected as test samples, and biological safety experiments were carried out according to the cell death / live staining, CCK-8 and hemolysis experiment standards. According to the GB / T16886.5 biomaterial evaluation standard, four different types of microneedle patch extracts were prepared, specifically including HP MN, HP@Z MN, HP@C MN and HP@CZMN; these extracts were used as culture media and co-cultured with PDLSCs, and cell death / live staining and CCK-8 experiments were used to evaluate the biocompatibility of the MN patches; in addition, the in vivo biological safety of the microneedle patches was detected by hemolysis experiments, and standard negative control (PBS) and positive control (ddH2O) were used in the hemolysis experiments to evaluate the effects of the extracts of HP MN, HP@Z MN, HP@C MN and HP@CZ MN four kinds of microneedle patches on the integrity of the erythrocyte membrane.

[0088] Figure 9 A, 9B are the cell death / or live staining images and quantification of the co-culture of four different types of microneedle patches with PDLSCs, Figure 9 C is the result of the CCK-8 cytotoxicity experiment of the co-culture of different groups of MN patches with PDLSCs. The results show that no significant inhibition of cell proliferation ability was observed after co-culture of the extracts of HP MN, HP@Z MN, HP@C MN or HP@CZ MN with PDLSCs, indicating that these extracts have no obvious cytotoxicity to PDLSCs. Figure 9 D is the result of the hemolysis experiment of different groups of MN patches. The extracts of HP MN, HP@Z MN, HP@C MN and HP@CZ MN four kinds of microneedle patches have no hemolytic effect on erythrocytes under the evaluated concentration and conditions, which is similar to the negative control (PBS), while the positive control (ddH2O) shows a strong hemolytic effect. These results provide important experimental basis for the safety and compatibility of these MN patches in biomedical applications.

[0089] 4. Antibacterial performance of HP@CZ MN in vitro

[0090] HP@CZ MN prepared in Example 1 and HP MN in Comparative Example 1 were selected as test samples, and in vitro antibacterial experiments of MN patches were carried out according to the bacterial colony counting, bacterial death / live staining and SEM experiment standards to verify their in vitro antibacterial performance.

[0091] Porphyromonas gingivalis (Pg) and Fusobacterium nucleatum (Fn) bacterial suspensions with a concentration of 1×10^6 CFU / mL were prepared and fully contacted with HP MN and HP@CZ MN, respectively. After incubation for 2 hours, the samples were diluted and 100 μL was spread on blood agar culture dishes and placed in an anaerobic incubator for culture. After a period of time, the colony growth was recorded by taking photos. The Pg and Fn bacterial suspension samples treated with the two MN patches were stained with a dead / live bacteria staining kit, and the bacterial survival was observed using an immunofluorescence microscope to intuitively reflect the antibacterial effect. At the same time, SEM was used to perform morphological analysis of the Pg and Fn bacteria treated with the two MN patches to observe the morphological changes of the bacteria under the action of HP MN and HP@CZ MN.

[0092] The results were compared and analyzed on the bactericidal effects of the Control group, HP group and HP@CZ group on periodontal pathogens Pg and Fn. Figure 10 shown. Figure 10 The MN patch showed the killing effect on these two bacteria. Figure 10 A and 10D respectively present the colony counts and quantitative analysis of Pg bacteria in different treatment groups. Figure 10 F and 10I are the corresponding data for Fn bacteria. The results showed that the HP@CZ group significantly reduced the number of bacteria compared with the Control group and the HP group. It is speculated that this enhanced effect can be attributed to the synergistic bactericidal effect of Cur. Further quantitative experiments strongly verified this inference. In the presence of PLMA, the microneedle patch showed excellent bactericidal performance, and the addition of Cur further enhanced the bactericidal effect. SEM was used to more intuitively observe the changes in bacterial morphology. Figure 10 B and 10G show the SEM images of the two bacteria after being treated with HP and HP@CZ, respectively. These images show that the bacterial cell membranes treated with HP or HP@CZ show obvious shrinkage, rupture and dissolution, which further proves the destructive effect of HP and HP@CZ on bacteria. In addition, the dead / alive staining of bacteria in different treatment groups was observed by fluorescence microscopy, combined with quantitative analysis. Figure 10 C and 10H respectively show the killing effect of HP and HP@CZ on these two bacteria, which is manifested by a decrease in the number of live bacteria and an increase in dead bacteria. This observation is consistent with the changes in bacterial morphology in the SEM image, further strengthening the above conclusions. In summary, the PLMA-containing microneedle patch (HP group and HP@CZ group) showed excellent killing effects on periodontal pathogens Pg and Fn, and the addition of Cur did play a significant role in synergistic antibacterial effects.

[0093] 5. In vitro immunomodulatory properties of HP@CZ MN

[0094] RAW264.7 cells in the logarithmic growth phase were selected and grouped according to the experimental design: one group was induced with lipopolysaccharide (LPS), and the remaining groups were treated with HP (LPS+HP), HP@Z (LPS+HP@Z), HP@C (LPS+HP@C), and HP@CZ (LPS+HP@CZ) microneedle patches respectively after LPS induction. After 24 hours of culture, the immunofluorescence staining technique was used to accurately label and analyze the changes in the expression levels of CD86 and CD206 in the cells. By comparing the expression ratio of CD86 / CD206, the distribution changes of F4 / 80, and the nuclear morphology labeled by DAPI, the polarization state of RAW264.7 cells under LPS induction and different treatment conditions was comprehensively observed. Further, the qRT-PCR technique was used to quantitatively analyze the expression levels of M1-type (including CD86, TNF-α, IL1β) and M2-type (including Arg-1, MCP-1, IL-10) polarization-related genes in RAW264.7 cells under LPS stimulation and subsequent different treatment conditions.

[0095] Figure 11 The evolution of the polarization state of RAW264.7 cells under LPS stimulation and subsequent treatment was shown. Figure 11 A, 11B presented the co-stained immunofluorescence images and fluorescence intensity statistics of F4 / 80, CD86, and DAPI in cells of different groups. Figure 11 C detected the expression levels of M1-type polarization-related genes in cells of each group by the qRT-PCR technique. Figure 11 D, 11E provided direct evidence of the M2-type polarization state again with the co-stained immunofluorescence images and fluorescence intensity statistics of F4 / 80, CD206, and DAPI. And Figure 10Figure F shows the expression levels of M2 polarization-related genes in each group of cells. The results showed that in the LPS group and the LPS+HP group, RAW264.7 cells exhibited strong CD86 fluorescence signals, indicating that they were mainly in the M1 polarization state, that is, the inflammatory response was significant. However, in the LPS+HP@Z, LPS+HP@C, and LPS+HP@CZ groups, the cells showed a significant decrease in CD86 fluorescence intensity, accompanied by a significant increase in CD206 fluorescence intensity, which marked the transformation of the cells from the M1 type to the M2 type polarization, reflecting the anti-inflammatory and repair characteristics. It is worth noting that the LPS+HP@Z group and the LPS+HP@CZ group containing ZIF-67 showed more significant effects in promoting M2 polarization of RAW264.7 cells, which further verified the core role of ZIF-67 in promoting M2 polarization of RAW264.7 cells. Among them, the LPS+HP@CZ group had the highest CD206 fluorescence intensity and the largest decrease in CD86. It is speculated that the reason why the HP@CZ group showed better effects than the HP@Z group may be because the Cur contained in it had a significant synergistic effect with ZIF-67, thus further enhancing its immunomodulatory performance. The qRT-PCR experimental data obtained the same conclusion. This finding not only reveals a new mechanism of cell polarization but also provides valuable inspiration for the development of future immunomodulatory drugs.

[0096] 6. Osteogenic properties of HP@CZ MN in vitro

[0097] Osteogenic induction medium (OIM) was introduced into PDLSCs respectively, and OIM combined with the extracts of different microneedle patches (HP, HP@Z, HP@C, HP@CZ) was used for induction and differentiation, aiming to explore the induction efficiency of HP, HP@Z, HP@C, and HP@CZ MN on the osteogenic differentiation of PDLSCs in the experiment.

[0098] When the cells were cultured for 7 days, the induced and differentiated cells were subjected to alkaline phosphatase (ALP) staining and activity detection. As Figure 12 shown in A, the ALP staining pictures of different treatment groups visually showed the osteogenic activities of each group. Among them, the staining of the OIM group and the HP group was relatively light, reflecting relatively low osteoblast activities; the staining depth of the HP@Z group was the same as that of the HP group, and no significant improvement was seen. However, the staining of the HP@C group and the HP@CZ group was significantly deepened, showing extremely high osteoblast activities, and this significant enhancement was attributed to the osteogenic promoting substance Cur in the two groups. As Figure 12 shown in B, the results of ALP activity detection further confirmed the above observations, clearly indicating that the HP@C and HP@CZ groups containing Cur showed excellent osteogenic induction ability under in vitro conditions and were excellent candidates for osteogenic materials.

[0099] To further evaluate the osteogenic differentiation potential of each treatment group at 14 days of induction, an alizarin red S (ARS) staining experiment was conducted. As Figure 12 shown in C, the intuitive osteogenic effect diagrams clearly presented the differences among the groups. Specifically, the staining areas of the OIM, HP, and HP@Z groups were lighter in color, with a limited number and low density of mineralized nodules, indicating a weak osteogenic differentiation ability. In contrast, the staining areas of the HP@C group and the HP@CZ group showed dark red colors, which marked the formation of a large number of dense mineralized nodules, predicting a significant enhancement of their osteogenic differentiation ability. Among them, the osteogenic effect of the HP@CZ group was particularly prominent, and the results of quantitative analysis ( Figure 12 D) further confirmed the above observations. This finding not only verified the significant osteogenic properties of Cur but also revealed the unique advantage of the slow and sustained release of Cur after encapsulation with ZIF-67. Given that osteogenesis itself is a long-term and complex process, this stable release property of Cur is undoubtedly more suitable for the exertion of its osteogenic effect, thus contributing to the excellent performance of the HP@CZ group in terms of osteogenic effect.

[0100] Test Example 4

[0101] To deeply explore the comprehensive therapeutic effect of HP@CZ MN in a SD rat periodontitis model, the following determinations were carried out. The experiment used 8-week-old male SD rats. After anesthesia, a periodontitis model was constructed through microsurgery and injection of a specific bacterial solution. Subsequently, HP, HP@CZ MN, and minocycline (Mino) were used for treatment, and the Sham group was set as the healthy control group, and PBS was used as the periodontitis group.

[0102] In terms of antibacterial performance, as Figure 13 shown in A results, compared with HP MN containing only PLMA, HP@CZ MN significantly enhanced its antibacterial effect by introducing ZIF-67 and Cur, exceeding the single antibacterial effect of PLMA and effectively reducing the bacterial load. In terms of anti-inflammatory and tissue repair, the ingenious introduction of ZIF-67 and Cur greatly improved the immunomodulatory efficacy of HP MN. The H&E staining results clearly showed (as Figure 12 shown in G) that compared with the HP group, the HP@CZ group had significant improvements in the regularity of nuclear arrangement, the stability of tissue structure, and the reduction of damage degree, indicating a stronger tissue recovery ability. In terms of osteogenesis, in this experiment, microCT technology was used to perform three-dimensional reconstruction of the alveolar bone loss degree of the maxillary second molar ( Figure 13(B), and comprehensively evaluated the treatment effects of each experimental group on periodontitis through quantitative analysis of key indicators such as the distance from the alveolar bone to the cementoenamel junction (CEJ-ABC), bone volume fraction (BV / TV), trabecular bone thickness (Tb.Th), and trabecular bone spacing (Tb.Sp). The experimental results showed that the HP@CZ group was superior to the Mino group in key bone tissue structure indicators such as CEJ-ABC ( Figure 13 (C), BV / TV ( Figure 13 (D), Tb.Th ( Figure 13 (E), and Tb.Sp ( Figure 13 (F), indicating that it was more effective in promoting bone tissue regeneration, increasing bone mass, and enhancing trabecular bone stability, and successfully reversed the bone tissue destruction trend caused by periodontitis. After encapsulation treatment with ZIF-67, Cur achieved stable and sustained release, and this characteristic greatly promoted the osteogenic effect of Cur.

[0103] In summary, HP@CZ MN demonstrated excellent comprehensive effects in the treatment of periodontitis and the promotion of alveolar bone repair. By introducing ZIF-67 and Cur, it not only enhanced the antibacterial performance of PLMA but also significantly improved the immunomodulatory efficacy of the patch, and achieved stable and sustained release of Cur, thus surpassing the clinically commonly used periodontitis treatment drug Mino in terms of treatment effect, providing new ideas and methods for periodontitis treatment.

[0104] It can be understood that the present invention is described through some embodiments. Those skilled in the art know that without departing from the spirit and scope of the present invention, various changes or equivalent replacements can be made to these features and embodiments. Additionally, under the teaching of the present invention, these features and embodiments can be modified to adapt to specific situations and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application belong to the scope protected by the present invention.

Claims

1. A composite nanoparticle with the ability of sequential release of active substances, characterized in that, The composite nanoparticles are Cur@ZIF-67NPs, with an average particle size of 403nm±7nm and a microstructure of dodecahedral particles with a rough surface texture. They have the functions of slowly releasing bioactive substances, improving the inflammatory microenvironment and regulating osteogenesis under certain conditions.

2. A multifunctional microneedle (MN) with the ability of sequential release of active substances, characterized in that, The MN comprises the Cur@ZIF-67NPs described in claim 1.

3. A multifunctional microneedle patch with the ability of sequential release of active substances, characterized in that, The multifunctional microneedle patch is HP@CZ MN, comprising a transparent substrate and yellow-brown MNs covering the surface of the substrate, wherein the MN is filled with the Cur@ZIF-67NPs as described in claim 1.

4. The multifunctional microneedle patch according to claim 3, characterized in that, The diameter of the substrate is 270 μm, the tip of the MN is 650 μm long, and the distance between the tips is 550 μm.

5. A method for preparing the multifunctional microneedle patch as described in claim 3, characterized in that, include: S1, fully dispersing curcumin powder in a solvent, adding ZIF-67 nanomaterials, allowing the ZIF-67 nanomaterials to coat the curcumin powder, washing and drying to obtain reddish brown solid Cur@ZIF-67NPs; S2, fully mixing methacryloyl hyaluronic acid (HAMA) and methacryloyl polylysine (PLMA) to obtain a mixed solution, and fully dispersing the Cur@ZIF-67NPs in the mixed solution to obtain a microneedle precursor solution; S3. The microneedle precursor solution is injected into the PDMS mold, and the mold is defoamed under negative pressure, dried and concentrated, and irradiated with a 405 nm light source to form a MN; then a 20% (w / v) polyvinyl alcohol (PVA) solution is added dropwise, dried to form a base, and demolded to obtain a multifunctional microneedle patch HP@CZ MN loaded with Cur@ZIF-67NPs.

6. The preparation method according to claim 5, characterized in that, The step S1 satisfies at least one of the following: (1) The mass ratio of the curcumin powder to the ZIF-67 nanomaterial is 1:200-1:300; (2) the mixing time of the curcumin powder and the ZIF-67 nanomaterial is 18 hours to 24 hours, and the reaction temperature is room temperature under normal pressure; (3) The drying conditions of the Cur@ZIF-67NPs are 120°C and the drying time is 24 hours to 36 hours.

7. The preparation method according to claim 5, characterized in that, The step S2 satisfies at least one of the following: (1) The final concentrations of HAMA and PLMA in the mixed solution are 2%-10%, and the final concentration values ​​are the same; (2) In the microneedle precursor solution, the mass fraction of Cur@ZIF-67NPs is 0.05wt%-1wt%.

8. The preparation method according to claim 5, characterized in that, In the process of preparing MN in step S3, at least one of the following is satisfied: (1) The negative pressure degassing operation and the drying and concentration operation are each performed twice, the negative pressure degassing time for a single time is 13 minutes to 25 minutes, the drying and concentration temperature is 30° C. to 37° C., and the drying and concentration time for a single time is 5 hours to 8 hours; (2) the microneedle precursor solution completely covers the needle tip of the PDMS mold; (3) Irradiate with a 405 nm light source for 10 to 20 seconds at room temperature and normal pressure.

9. The preparation method according to claim 5, characterized in that, During the process of preparing the substrate in step S3, the drying time is 24 hours to 48 hours.

10. An application of HP@CZ MN, prepared by the preparation method described in any one of claims 5-9, characterized in that, The application of the HP@CZ MN in the adjuvant treatment of periodontitis includes at least one of the following: (1) Antibacterial; (2) Regulate the inflammatory microenvironment; (3) Promote osteogenic differentiation.

Citation Information

Cited By

  • Sterilization and anti-inflammation multi-layer microneedle patch with programmed response and preparation method of sterilization and anti-inflammation multi-layer microneedle patch

    CN121533969A

  • A bactericidal and anti-inflammatory multi-layer microneedle patch with programmed response and a preparation method thereof

    CN121533969B